2012
DOI: 10.1111/j.1528-3585.2012.00489.x
|View full text |Cite
|
Sign up to set email alerts
|

It's a Family Affair: Germany as a Responsible Actor in Popular Culture Discourse

Abstract: In 2001, Afghanistan became a threat to Germany, an act of “writing security” that resulted in a strong Bundeswehr involvement in military missions. But to defend itself at the Hindu Kush in such a proactive way seems to be at odds with the noninterventionist history and identity of the Federal Republic. This identity conflict is reflected in a fierce and ongoing discourse on foreign deployments and Germany's identity as a responsible actor in world politics. This article looks into representations of this ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Similarly, the analysis demonstrates the importance of gender constructions in the legitimation of military operations, as many of the visual representations draw on established discursive practices from gender discourse for legitimacy. Aside from a few exceptions (Engelkamp and Offermann 2012;Schoenes 2011), this aspect has been neglected altogether in the study of German foreign and security policy. Given the centrality of gender(ed) constructions for the legitimation of violence in international politics, highlighted by feminist security studies, scholars of German foreign and security policy need to pay much more attention to this aspect.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the analysis demonstrates the importance of gender constructions in the legitimation of military operations, as many of the visual representations draw on established discursive practices from gender discourse for legitimacy. Aside from a few exceptions (Engelkamp and Offermann 2012;Schoenes 2011), this aspect has been neglected altogether in the study of German foreign and security policy. Given the centrality of gender(ed) constructions for the legitimation of violence in international politics, highlighted by feminist security studies, scholars of German foreign and security policy need to pay much more attention to this aspect.…”
Section: Resultsmentioning
confidence: 99%
“…Mango Dreams expresses these dimensions metaphorically through family relations as a discursive site of rift and reunion. 63 We found three different but related conceptualizations of peace. Firstly, peace is imagined as a possibly utopian place of destination but also a contested site of struggle-it is both a state and a process.…”
Section: Resultsmentioning
confidence: 89%
“…117–118) argued that popular culture contributes to the reproduction and popularization of official foreign policy discourses and state actions, while at the same time providing a site for contesting official state narratives. It has been shown that artifacts of popular culture shape “society members’ beliefs, attitudes, and emotions” (Bar-Tal, 2013, p. 132), and they may legitimize and justify wars and military interventions by normalizing war crimes or representing them as “inevitable” (Engelkamp & Offermann, 2012). As Weldes (1999, p. 119) states, popular culture may help to “produce consent for foreign policy and state action.” As an example of it, this article shows how comics published by CNMH aim to produce consent for the peace process and restitution of lands to displaced peasants by (re)producing a neoliberal discourse.…”
Section: Collective Memorymentioning
confidence: 99%